Proponer nuevas formas de consumo de la bebida autóctona de la ciudad de Otavalo (chicha del yamor), mediante su uso en el área de la repostería - Paida Flores, Luis Eduardo (2020)
This investigation deals with the feasibility study for the creation of a gamer-style themed restaurant, which seeks to satisfy the needs of new nascent markets thanks to technological evolution, these markets have come to be frowned upon by today's society and by therefore they cannot find their comfort place. In the 20th century era, a terminology was born that is related to the new technological trends emerging at that time, the so-called 'millennials' who are people who were born and raised in an environment of great technological use\; The “Cyber” market stands out in this segment, which are those individuals who love technology and its services, leading to the growing gamer era. The presence of the famous video games has currently made an impact in today's society, but still remains a segment that is not treated with the attention it deserves. Gastronomy, being a basic necessity in human beings, has not been able to completely satisfy the needs of the previously seen market. According to previous research, the gamer market segment has not found a suitable place, highlighting that the creation of Internet cafes was a possible solution. . For the creation of a gamer restaurant, previous methods would be needed, which would facilitate the investigation, such as the inductive-deductive method that supported with the appropriate pertinent information, the analytical-synthetic method determining objectivity and the study of the problem and the qualitative-quantitative method developing an analysis of market behavior both morally and financially. To achieve the objectivity of the methods, the use of appropriate techniques for the sector was determined, such as: surveys, interviews and observation sheets, which gave a positive result from the reception of the local assumption to the impact on the market, contributing to previous research, since information is scarce, more attention is expected to gastronomic and tourist services of this nature.